Effect of Individual Cognitive Stimulation Therapy on Dementia and Quality of Life in Older Adults: A Quasi-experimental Study - Pooja Motar Sublok; Mrunali Kerkar; Shivani Patil; Bhairavi Ugale (Journal of Clinical and Diagnostic Research)
Introduction: Dementia is a chronic neurocognitive disorder that causes a decline in cognitive functions. As the global prevalence of dementia rises, non pharmacological therapies, such as Cognitive Stimulation (CS), have shown promise in preserving cognitive function and improving Quality of Life (QoL). Individual Cognitive Stimulation Therapy (iCST) offers an alternative intervention for those unable to participate in group therapies, often involving caregivers as facilitators. Aim: To evaluate the effect of iCST on dementia in older adults and its impact on individual QoL. Materials and Methods: This quasi-experimental trial, a pre-post study design was conducted in Marathwada, Aurangabad, Maharashtra, India, from September 26, 2023 to February 21, 2024. A total of 34 study participants, aged ≥60 years with mild to moderate dementia {Global Clinical Dementia Rating (CDR) score=1 or 2}, were included. Participants received iCST three times a week, with each session lasting 45 minutes, over a period of five weeks. After the completion of therapy, changes were noted using the Clinical Dementia Rating (CDR) scale and the Older People’s Quality Of Life (OPQoL) questionnaire. Data were analysed using the Shapiro-Wilk test and the dependent t-test. Results: The results were statistically significant with respect to both measures. The mean difference of the CDR Scale and the OPQoL questionnaire score was 0.97±1.28 and 10.79±5.31, respectively which showed a statistically highly significant difference with a p-value <0.001. Conclusion: The iCST program has shown efficacy in alleviating dementia symptoms and enhancing the QoL for individuals with mild to moderate dementia.